Copy number variation analysis of the 17q21.31 region and its role in neurodegenerative diseases. Issue 2 (9th October 2015) - Cervera‐Carles, Laura; Pagonabarraga, Javier; Pascual‐Sedano, Berta; Pastor, Pau; Campolongo, Antonia; Fortea, Juan; Blesa, Rafael; Alcolea, Daniel; Morenas‐Rodríguez, Estrella; Sala, Isabel; Lleó, Alberto; Kulisevsky, Jaime; et al.
Abstract : The H1 haplotype of the 17q21.31 inversion polymorphism has been consistently associated with progressive supranuclear palsy, corticobasal degeneration, and Parkinson's disease in Caucasians. Recently, large polymorphic segmental duplications resulting into complex rearrangements at this locus with a high diversity range in human populations have been revealed. We sought to explore whether the two multi‐allelic copy number variants that are present in the H1 clade (with segmental duplications of 300 and 218 kilobases in length) could be responsible for the known H1‐related risk of developing these neurodegenerative disorders. A total of 857 Spanish subjects including 330 patients with Parkinson's disease, 96 with progressive supranuclear palsy, 55 with corticobasal degeneration, 51 dementia with Lewy bodies, and 325 neurologically healthy controls, were genotyped for the H1/H2 haplotype. Subsequently, the two copy number variants that are characteristic of the H1 haplotype were evaluated through a high‐resolution approach based on droplet digital polymerase chain reaction, in all H1 homozygous subjects. The H1 allele was significantly overrepresented in all diagnostic groups compared with controls (Parkinson's disease, P  = 0.0001; progressive supranuclear palsy, P  = 1.22 × 10 −6 ; corticobasal degeneration, P  = 0.0002; and dementia with Lewy bodies, P  = 0.032). However, no dosage differences were found for any of the two copy number variants analyzed. The H1 haplotype is associated with the risk of several neurodegenerative disorders, including dementia with Lewy bodies. However, common structural diversity within the 17q21.31‐H1 clade does not explain this genetic association. © 2015 Wiley Periodicals, Inc.